Analysis of a DSP-system in order to flexibly control a switch mode power supply - Dürbaum, Thomas; et al. (12th European Conference on Power Electronics and Applications - EPE 2007, 2 - 5 September 2007, Aalborg, Denmark, 2007)
This paper investigates a DSP-platform for the purpose to control a switch mode power supply digitally. As the PWM module and the A/D-converter are the interfaces of the digital controller to the analog power supply, both modules will be examined with regard to their performance but also to possible sources of errors. As occurring delay times in the digital controller will have an effect on the stability, the delay times will be calculated and verified by small signal measurements.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.analys
Keywords: DSP; Power management; Pulse Width Modulation (PWM); Test bench